FATORES DETERMINANTES DA SOBREVIVÊNCIA DAS MICRO E PEQUENAS EMPRESAS DO SETOR INDUSTRIAL NA CIDADE DE SANTOS - Colmenero, Márcio Roberto Paz (2013)
The importance of micro and small companies in the Brazilian economy is already felt in a long time, because this segment is critical in generating wealth for society. Despite the economic importance, there is still a high degree of discontinuity in the same, which gives them difficulties in crossing the two first and most critical years of existence. This research aims to identify the determinants of survival of micro and small enterprises in the industrial sector in the city of Santos. The relevance of the study is intensified due to the city of Santos to be experiencing a moment of economic development driven by oil discoveries in the pre -salt. This may further increase the number of creation MSE, primarily in the industrial sector, which are likely to need information on which to look up. The study is exploratory and descriptive. Data were collected through a field survey with a questionnaire based on four dimensions: entrepreneurship, environmental, financial and internal organization. The research presented as key factors for survival time dedicated to the company, the adequacy of product demand, the ability to take risks and lead manager. The study sample was defined by convenience, consists MSE belonging to the industrial economic sector because it is more adherent to the chain of oil exploration. We considered companies that surpassed the first two years of existence, in accordance with the evaluation criteria adopted by SEBRAE Survival (2011).